Penataan Ruang Wilayah Pesisir sebagai Upaya Mitigasi Bencana Tsunami di Pantai Watu Pecak, Kabupaten Lumajang - Kurnia Maulidi Noviantoro; Herry Rachmat Widjaja; Masri Ridwan (Jurnal Wilayah dan Lingkungan, 2022)
Spatial planning for coastal areas is a logical effort that can be done in tsunami disaster mitigation. Including the management of the coastal area of Watu Pecak, Lumajang district which has the potential to be hit by the disaster. The purpose of this study was to map the ideal spatial arrangement in the Watu Pecak beach area, Lumajang Regency, East Java as an effort to mitigate the tsunami disaster. The research was conducted in July-August 2021. This study uses a qualitative method with a descriptive approach. The data collection was done through observation, in-depth interviews, and documentation. Data analysis was carried out with the help of geogle earth image interpretation, then the identification results were reviewed descriptively along with the results of surveys, interviews, and other secondary sources. The research findings explain that the spatial planning of the Watu Pecak coastal area needs to be done. Spatial planning recommendations that urgently need to be implemented for tsunami mitigation include planting mangroves as a green belt, constructing a coastal embankment (breakwater), improving the position and relocation of settlement, as well as developing an early warning system and to complete coastal sign system.